SiC junction enhanced carbon nanofiber aerogels with extremely high specific strength and ultra-low thermal conductivity. Issue 8 (July 2023) - Dang, Wei; Zhao, Linna; Li, Fuping; Li, Chenxi; Xu, Zhuoli; Zhang, Xinyuan; Zhao, Kang; Tang, Yufei
Abstract: C/SiC aerogels with both ultra-low thermal conductivity and extremely high strength were fabricated by freeze casting. SiC junctions originated from pyrolysis of polycarbosilane (PCS) were formed between carbon nanofibers (Cf ) to enhance the strength of aerogels. The effects of PCS content and total solid content on the phase composition, pore structure, thermal conductivity and compressive property were studied. The fabricated aerogels possess hierarchical pore structure. In the micro-scale, it contains circular pores with size of about 15 µm, while it is mesoporous and macroporous in the nano-scale. Both thermal conductivity and compressive strength increase with the increase in PCS content. Through tailoring PCS content and total solid content, Cf /SiC aerogels with porosity of 99.5%, thermal conductivity of 33 mW·m −1 ·K −1 and compressive strength of 7.14 MPa can be obtained. The specific strength of the fabricated Cf /SiC aerogels is up to 467.6 MPa/(g/cm 3 ), which is the highest value for ceramic aerogels.